Capitalismo editorial: do papel à nuvem - Nojosa, Urbano Nobre (2017)
The thesis Capitalism: from paper press to cloud heralds the relationship between capitalism and social communication because the 2008 economic and financial crisis revealed the plot among the advertising industry, journalistic media outlets and social networks in the web as elements that constitute capital super production and turnover of higher organic composition. It is expressed by international financial capital, which transforms global economy and wealth through securitization into speculative and volatile bonds. This economic and political crisis displays a gambling logical construction, permeated by drug trafficking money, corruption and fraud by corporations. Journalism became the area for capitalist doxa legitimation, playing the role of public doxa that generates consensus. That is, the articulation between good sense and common sense that guides the individual in order to follow the social programming and regularity, to forge total life control, to order daily life according to the social rder values. These fill in tasks, behaviours and rules previously orchestrated by the domination power of capitalism. Modern lifestyle leverages the production and consumption of goods liturgy, which are exposed and worshiped by the media activity. The media undertakes a religious character of expanding and connecting the world, individuals and God in a common movement. Media takes on the role of creating consensus mediation, which results in a pacified unity between discourse standardization and politics. Endoxa is this consensus, the will of the majority, a general will that results in the ideas of subject, consciousness and identity. Therefore, the modern national state project forwarded by the encyclopaedists and the bourgeois revolution slides into a philosophy of the media that involves a philosophical questioning of the writing culture tradition, confronted with digital narrative experiences in the internet, big data use, machine learning and business intelligence. Modern press has become the catalyst of a unique cultural, political and communication process in human history. Press has reshaped the lives of millions of workers and peasants that legitimated the French bourgeoisie actions confronting the previous political regime. The political world is moving again with the Arab Spring in the Middle East and North Africa, Occupy Wall St in the US and Los Indignados in Spain. These protests are identified as the first street demonstrations organized using social networking, mediated by Facebook. These are demonstrations of millions of workers and young people facing the globalization of late capitalism and international crisis. Let’s move forward!